Plasma osteopontin relates to myocardial fibrosis and steatosis and to immune activation among women with HIV. (1st February 2023) - Robinson, Jake A.; Toribio, Mabel; Quinaglia, Thiago; Awadalla, Magid; Talathi, Ria; Durbin, Claudia G.; Alhallak, Iad; Alagpulinsa, David A.; Fourman, Lindsay T.; Suero-Abreu, Giselle Alexandra; Nelson, Michael D.; Stanley, Takara L.; et al.
Abstract : Objective: Women with HIV (WWH) have heightened heart failure risk. Plasma OPN (osteopontin) is a powerful predictor of heart failure outcomes in the general population. Limited data exist on relationships between plasma OPN and surrogates of HIV-associated heart failure risk. Design: Prospective, cross-sectional. Methods: We analyzed relationships between plasma OPN and cardiac structure/function (assessed using cardiovascular magnetic resonance imaging) and immune activation (biomarkers and flow cytometry) among 20 WWH and 14 women without HIV (WWOH). Results: Plasma OPN did not differ between groups. Among WWH, plasma OPN related directly to the markers of cardiac fibrosis, growth differentiation factor-15 ( ρ = 0.51, P = 0.02) and soluble interleukin 1 receptor-like 1 ( ρ = 0.45, P = 0.0459). Among WWH (but not among WWOH or the whole group), plasma OPN related directly to both myocardial fibrosis ( ρ = 0.49, P = 0.03) and myocardial steatosis ( ρ = 0.46, P = 0.0487). Among the whole group and WWH (and not among WWOH), plasma OPN related directly to the surface expression of C-X3-C motif chemokine receptor 1 (CX3CR1) on nonclassical (CD14 − CD16 + ) monocytes (whole group: ρ = 0.36, P = 0.04; WWH: ρ = 0.46, P = 0.04). Further, among WWH and WWOH (and not among the whole group), plasma OPN related directly to the surface expression of CC motif chemokine receptor 2 (CCR2) on inflammatory (CD14 + CD16 + ) monocytes (WWH: ρ = 0.54, P = 0.01; WWOH: ρ = 0.60, P = 0.03), and in WWH, this held even after controlling for HIV-specific parameters. Conclusion: Among WWH, plasma OPN, a powerful predictor of heart failure outcomes, related to myocardial fibrosis and steatosis and the expression of CCR2 and CX3CR1 on select monocyte subpopulations. OPN may play a role in heart failure pathogenesis among WWH. Clinicaltrials.gov Registration: NCT02874703.